Curriculum Management in Early Childhood Education - Frinza, Frinza; Kristiawan, Muhammad; Houtman, Houtman (Journal of Social Work and Science Education, 2020)
Potential Early childhood can be developed through proper planning, implementation and evaluation of the learning curriculum. This paper is a qualitative study which carried out in-depth observations at TKIT Islahul Ummah Prabumulih City. The results obtained indicate that PAUD learning activities begin with 1) curriculum planning starting from meetings attended by all educators, making annual and semester program curriculum plans as well as the design of weekly activities and the design of daily activities; 2) curriculum implementation has used in door activity and out door activity; 3) curriculum evaluation is carried out periodically and has been set a time, every once a month parents of students are invited to discuss and talk about learning that has been done one month before. This paper provides new insight for implementation of curriculum management for early childhood education should refer to the national curriculum with additional Islamic religious material where we could have character building for our student.